Pengembangan Media Pembelajaran Virtual Reality (VR) Pada Materi Tata Surya di Kelas VI Sekolah Dasar - Yuliska, Adilla; Tahyra, Jihan; Amas, Miftahul Khoiri (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
This study aims to determine how the process of developing Virtual Reality (VR) media in learning science solar system material for grade VI elementary school students. This research method uses the Research and Development (R&D) research method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques in this study were interviews and filling out questionnaires conducted with 10 students and 3 elementary school students. The result of this research is to produce a Virtual Reality (VR) development product on solar system material. The implications of using VR media not only increase student understanding, but also have the potential to change teacher teaching methods.